In Vivo and In Vitro Antidiabetic Efficacy of Aqueous and Methanolic Extracts of Orthosiphon Stamineus Benth - Najlaa Bassalat; Sleman Kadan; Sarit Melamed; Tamar Yaron; Zipora Tietel; Dina Karam; Asmaa Kmail; Mahmud Masalha; Hilal Zaid (MDPI AG, 2023)
Orthosiphon stamineus is a popular folk herb used to treat diabetes and some other disorders. Previous studies have shown that O. stamineus extracts were able to balance blood glucose levels in diabetic rat animal models. However, the antidiabetic mechanism of O. stamineus is not fully known. This study was carried out to test the chemical composition, cytotoxicity, and antidiabetic activity of O. stamineus (aerial) methanol and water extracts. GC/MS phytochemical analysis of O. stamineus methanol and water extracts revealed 52 and 41 compounds, respectively. Ten active compounds are strong antidiabetic candidates. Oral treatment of diabetic mice with O. stamineus extracts for 3 weeks resulted significant reductions in blood glucose levels from 359 ± 7 mg/dL in diabetic non-treated mice to 164 ± 2 mg/dL and 174 ± 3 mg/dL in water- and methanol-based-extract-treated mice, respectively. The efficacy of O. stamineus extracts in augmenting glucose transporter-4 (GLUT4) translocation to the plasma membrane (PM) was tested in a rat muscle cell line stably expressing myc-tagged GLUT4 (L6-GLUT4myc) using enzyme-linked immunosorbent assay. The methanol extract was more efficient in enhancing GLUT4 translocation to the PM. It increased GLUT4 translocation at 250 µg/mL to 279 ± 15% and 351 ± 20% in the absence and presence of insulin, respectively. The same concentration of water extract enhanced GLUT4 translocation to 142 ± 2.5% and 165 ± 5% in the absence and presence of insulin, respectively. The methanol and water extracts were safe up to 250 µg/mL as measured with a Methylthiazol Tetrazolium (MTT) cytotoxic assay. The extracts exhibited antioxidant activity as measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. O. stamineus methanol extract reached the maximal inhibition of 77 ± 10% at 500 µg/mL, and O. stamineus water extract led to 59 ± 3% inhibition at the same concentration. These findings indicate that O. stamineus possesses antidiabetic activity in part by scavenging the oxidants and enhancing GLUT4 translocation to the PM in skeletal muscle.